Determination of economic upper limit of drying processes in coal-fired power plants - Akkoyunlu, Mustafa Tahir; Erdem, Hasan Huseyin; Pusat, Saban (TAYLOR & FRANCIS INC, 2016)
In this study, the economic assessment of coal drying prior to ga rinding mill process in coal-fired thermal power plants was carried out. In the literature, despite the fact that there are studies regarding drying systems, the advantages and disadvantages of these systems in comparison to each other and the benefits that drying will provide, and the economic factors that are the most important determinants in the practice of the drying system, were not adequately analyzed. In this study, on the other hand, a model was developed to determine the necessary critical cost point in order to identify the appropriate drying system. Through the use of this model, the benefits to be gained from the planned drying system and the financial upper limit required for this investment can be specified. As a model application, eight of the thermal power plants in Turkey were examined. The economic upper limit of a drying system to enable coal to be dried at a rate of 10% was determined through a model study carried out for Catalagzi Power Plant.
Keywords: Coal; drying; moisture; power plants; LOW-RANK COALS; PROXIMATE ANALYSIS; HEATING VALUES; LIGNITE; BED; TEMPERATURE; TECHNOLOGIES; EFFICIENCY; MICROWAVE; CHINESE; Engineering